Cytotoxic effects of bioceramic materials on stem cells from human exfoliated deciduous teeth (SHED) - Oliveira, Bárbara Luísa Silva; Silveira , Ana Beatriz Vieira da; Bergamo , Mariel Tavares Oliveira Prado; Ambrosio, Eloá Cristina Passucci; Jorge , Paula Karine; Bringel , Mayara; Lourenço Neto , Natalino; Machado, Maria Aparecida Andrade Moreira; Oliveira, Thais Marchini (Brazilian Dental Science, 2024)
Objective: This study aimed to evaluate stem cell from human deciduous teeth (SHED) viability after exposure to different bioceramic materials. Material and Methods: Discs were constructed to obtain the material extracts according to the following groups: G1 - Bio-C Repair, G2 - MTA Repair HP, G3 - TheraCal LC, and G4 – Biodentine. Positive and negative control group were respectively maintained with alphaMEM + 10% FBS and alphaMEM + 1% FBS. SHED obtained through primary culture were in contact with material extracts for 24, 48, and 72h. MTT assay evaluated cell viability. Groups were plated in triplicate and the cell viability assay were repeated three times. Data were analyzed by two-way ANOVA followed by Tukey test (p